Soil oribatid mite (Acari: Oribatida) diversity and composition in semi-deciduous forest fragments in eastern Amazonia and comparison with the surrounding savanna matrix - Ferreira, Raimundo Nonato C.; Franklin, E.; Souza, Jorge Luiz Pereira; Moraes, Jamile de (Journal of Natural History, 2012)
We recorded species abundance and richness of oribatid mites along 16 plots established in semi-deciduous forest fragments in Amazonia. The results were compared with a published dataset consisting of an inventory carried out in 38 plots in the surrounding savanna. Totals of 143 and 91 species were recorded in the forest fragments and savanna, respectively. Sørensen similarity index between both environments was 0.44. Ordination of sites according to oribatid mite species composition showed a clear separation between forest fragments and savanna. Rostrozetes ovulum, Archegozetes longisetosus and Eohypochthonius (Eohypochthonius) becki were abundant and frequent in the forest fragments but exceedingly rare in the savanna. Neoppia (Neoppia) schauenbergi, Pseudoppia sp. C, Microppia sp. A and Cosmochthonius sp. A were limited to the savanna. This study also represents an early step toward knowing which groups of species are exclusive to one or another vegetation type or are sensitive to their inherent environmental conditions. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: Abundance; Comparative Study; Data Set; Deciduous Forest; Forest Inventory; Mite; Savanna; Sensitivity Analysis; Soil Fauna; Species Diversity; Species Richness; Vegetation Type; Amazonia; Acari; Archegozetes Longisetosus; Eohypochthonius; Oribatida; Rostrozetes